Sistem Pendukung Keputusan Penerima Beasiswa Menggunakan Metode Simple Multi Attribute Rating Technique (SMART) - Muhammad Risco Ramadhan; Fiftin Noviyanto (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Scholarships is a form of appreciation and giving in the form of financial support distributed to individuals with the aim of fulfilling the sustainability of the level of education being undertaken. University has provided various scholarships with various criteria for its students, but scholarships have their own goals and targets, namely, students who really fit the criteria required by the scholarship so that scholarships can be right on target according to the wishes of the organizers. For these purposes, proper analysis and calculations are needed, but scholarship selection is still done manually, so it takes quite a long time and the results calculated manually are less objective and not transparent. To solve this problem, a decision-support system was built to determine the selection of scholarship recipients. The system built using a decision support system using the simple multi-attribute rating technique (SMART) method was used to handle multi-criteria problems. The decision-making method is aimed at criterion problems that have many values owned by each alternative in each of the criteria that have calculated weight values. The research process was carried out using the Waterfall Modified approach to ensure that the output of the research product can run well, and the usability value and user experience are good. The process of evaluating the research output was carried out using the Blackbox approach and System Usability Scale approach. The results of the evaluation of the system achieved an average value above the standard to achieve usability and user experience goals.